2020
DOI: 10.1002/hsr2.222
|View full text |Cite
|
Sign up to set email alerts
|

A child with sickle cell disease can't live with just anyone.” A mixed methods study of socio‐behavioral influences and severity of sickle cell disease in northern Nigeria

Abstract: Background The modulatory effects of psychosocial and biophysical environments on sickle cell disease (SCD) severity during childhood has not been well characterized in high burden settings, such as Nigeria. Objectives We identified socio‐demographic correlates and explored caregivers' perceptions on socio‐behavioral and environmental influences on hospitalization for pain and blood transfusion of children with SCD in Kano, Nigeria. Methods U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…53,54 Other studies have identified socio-behavioral, psychological, and environmental factors that may impact disease severity, indicating a more complex and bidirectional relationship. 55 The lack of a gold standard measure of disease severity in SCD likely accounts for discrepancies between studies investigating this variable. Sixty-five percent of children included in our study had immigrated to Canada (on average living in Canada for 4 years), and these results suggest that perhaps with more time living in Canada, social difficulties may subside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Other studies have identified socio-behavioral, psychological, and environmental factors that may impact disease severity, indicating a more complex and bidirectional relationship. 55 The lack of a gold standard measure of disease severity in SCD likely accounts for discrepancies between studies investigating this variable. Sixty-five percent of children included in our study had immigrated to Canada (on average living in Canada for 4 years), and these results suggest that perhaps with more time living in Canada, social difficulties may subside.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited, past work has shown that a more severe disease status is related to poorer overall HRQL 53,54 . Other studies have identified socio‐behavioral, psychological, and environmental factors that may impact disease severity, indicating a more complex and bidirectional relationship 55 . The lack of a gold standard measure of disease severity in SCD likely accounts for discrepancies between studies investigating this variable.…”
Section: Discussionmentioning
confidence: 99%
“…The Impact of Men's Involvement in the Management of Sickle Cell Anemia Sickle cell anemia, a genetically inherited blood disorder, has historically been perceived as a predominantly female concern, largely associated with maternal roles, childcare, and family caregiving [33]. However, as our understanding of the disease has evolved, so too has the recognition of the pivotal role that men can play in its comprehensive management.…”
Section: ©Nijses Publicationsmentioning
confidence: 99%
“…42,45 Findings from this study revealed some psychosocial impacts of sickle cell disease. 70 Societal attitudes and perceptions were identified as triggers for major psychosocial issues among sickle cell disease patients. Impaired psychosocial health-related quality of life had been associated with a number of negative effects, including low self-esteem; anxiety and depression; a loss of interest in basic life activities.…”
Section: Dovepressmentioning
confidence: 99%